2006
DOI: 10.1364/oe.14.009780
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of asymmetric bacteria utilizing electro orientation

Abstract: Abstract:We propose a bacterial detection scheme which uses no biochemical markers and can be applied in a Point-of-Care setting. The detection scheme aligns asymmetric bacteria with an electric field and detects the optical scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…31 We utilize the same parameters as have been shown in the electro-orientation techniques of E. coli K12 described in previous work to align the bacteria to the electric field. 17 10 V pp at 10 MHz is applied across two electrodes to obtain a preferred alignment. Live bacteria is flowed horizontally from right to left within the microfluidic channel at a rate of 20 mm s À1 .…”
Section: Experiments 41 Electro-orientation Within a Fluidic Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…31 We utilize the same parameters as have been shown in the electro-orientation techniques of E. coli K12 described in previous work to align the bacteria to the electric field. 17 10 V pp at 10 MHz is applied across two electrodes to obtain a preferred alignment. Live bacteria is flowed horizontally from right to left within the microfluidic channel at a rate of 20 mm s À1 .…”
Section: Experiments 41 Electro-orientation Within a Fluidic Channelmentioning
confidence: 99%
“…[11][12][13][14][15][16] Recent studies of electro-orientation have revealed its ability to orient bacteria and nanowires. [17][18][19] Dielectrophoresis provides for concentration and sorting capabilities 11,12,16 and electro-orientation allows for the alignment of asymmetric particles on a macro scale. 20 Several methods for integration of electrodes with microfluidic channels have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Electro-orientation was applied to the study of several types of cells such as red blood cells 12,14 and bacteria. 15 Recently, it was reported that electro-orientation occurred during the OET manipulations of nanowires 9 and red blood cells. 11 Figures 3͑a͒-3͑d͒ show a typical alignment behavior of swimming cells in the grayscale OET.…”
Section: Programmable Manipulation Of Motile Cells In Optoelectronic mentioning
confidence: 99%
“…Various mechanisms for the reconfigurability have been realized with the application of external forces. Electrical forces have been utilized to tune a liquid lens, align birefringent material and attract or repel electronic ink [2][3][4]. Mechanical forces have been utilized to stretch and compress liquid dye laser gratings and to pneumatically pump liquid [5][6][7].…”
Section: Introductionmentioning
confidence: 99%